Genes of Helicobacter pylori Regulated by Attachment to AGS Cells - Kim, Nayoung (American Society for Microbiology, 2004)
Reciprocal interactions between Helicobacter pylori and cells of the gastric epithelium to which it adheres may affect colonization. Changes in gene expression of H. pylori induced by adhesion to AGS gastric cancer cells by coculture were compared to changes in gene expression of H. pylori cultured without AGS cells by using cDNA filter macroarrays. Adhesion was quantitatively verified by confocal microscopy of green fluorescent protein-expressing bacteria. Four experiments showed that 22 and 21 H. pylori genes were consistently up- and down-regulated, respectively. The up-regulated genes included pathogenicity island, motility, outer membrane protein, and translational genes. The σ(28) factor antagonist flgM, flgG, the stress response gene, flaA, omp11, and the superoxide dismutase gene (sodB) were down-regulated. The up-regulation of cag3, flgB, tonB, rho, and deaD was confirmed by quantitative PCR, and the up-regulation of lpxD, omp6, secG, fabH, HP1285, HP0222, and HP0836 was confirmed by reverse transcription (RT)-PCR. The down-regulation of flaA, sodB, and HP0874 was confirmed by quantitative PCR, and the down-regulation of omp11 was confirmed by RT-PCR. The alteration of gene expression in H. pylori after adhesion to gastric cells in vitro suggests that changes in motility, outer membrane composition, and stress responses, among other changes, may be involved in gastric colonization.